HUBUNGAN KOMPONEN HEALTH BELIEF MODEL (HBM) DENGAN TINDAKAN PENGGUNAAN KONDOM PADA ANAK BUAH KAPAL (ABK) DI PELABUHAN BELAWAN TAHUN 2017 - Suprapto Suprapto (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
The rate of HIV spread tends to be increasing. The highest risk factor of HIV spread is through sexual intercourse because many of those belong to the sexual-risk behavior group do not use condom. One of those belong to the sexual-risk behavior groups is the ship crew who become the customers of commercial sex workers (prostitutes) The purpose of this study with cross-sectional design was to examine the relationship between the concept of Health Belief Model (HBM) and condom-using behavior in the ship crew who become the customers of commercial sex workers (prostitutes) in Belawan Seaport. The samples for this study were 95 persons selected through consecutive sampling technique. The data of this study were statistically tested by using Chi-square test. The relationship between independent and dependent variables was determined based on Prevalence Ration (PR) at Confidence Interval (CI) 95% and was analyzed through multiple logistic regression tests. The result of this study showed that the proportion of condom use in the ship crew was still low (74,7%). The result of Chi-square test showed that there were 5 components of HBM which were significantly related to the condom-using behavior, namely, stimulus from the commercial sex workers (p = 0.010), knowledge (p = 0.043), Perceived severity (p = 0.000), perceived benefit (p = 0.000) and perceived self efficacy (p = 0.000). The result of logistic regression analysis showed that perceived benefit was the most dominant factor relating to the condom-using behavior in the crew of ship at Belawan Seaport in 2017. To improve the condom-using behavior in the ship crew, it is recommended to make the use of condom 100% compulsory for the ship crew who become the customers of commercial sex workers especially when they are in the localization complex, to socialize condom, to distribute condom, to improve the bargaining power of the commercial sex workers in negotiating the use of condom, and to raise the awareness of the ship crew to use condom. Key words : Condom, HBM, Ship Crew